Contact with Scandinavian and late Middle English negative concord - Ingham, Richard (Adam Mickiewicz University, 2008)
Early Modern English saw negative concord disappear from the mainstream textual record (Nevalainen 1998; Kallel 2005), which may embody natural language change rather than prescriptivist pressure (Mazzon 1994). This study examines whether there is evidence that the change began in some Northern varieties of English, and if so whether it is attributable to Scandinavian influence. Data from 14th century verse show some weakening of NC in Northern verse, but not in corresponding southern variety texts, supporting the findings of Ingham (2006a) for late Middle English prose, contra Iyeiri (2002). Early Scandinavian verse data are shown to present a similar weakening of NC. These results are interpreted in terns of Jespersen’s (1917) negation cycle, to the effect that Scandinavian varieties were in advance of early English on the negation cycle, were losing NC at the time of the Scandinavian ingressions into England, and that their influence on Northern Middle English contributed to the weakening of NC earlier in the North than in the rest of England.